Pengembangan Media Edukasi Video Animasi Sebagai Pendamping Ibu dan Kader Dalam Pemberian Makan Balita - Sri Lestari Kartikawati; Intan Yusita; Ina Sugiharti (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Nutrition during the First 1,000 Days of Life (DOHaD) is crucial for growth and development and is key to stunting prevention. However, field observations indicate that mothers and Posyandu cadres (community health workers) often face limited knowledge, educational media, and communication skills. The primary challenge is the low adherence to Complementary Feeding MP-ASI (guidelines regarding timely initiation, texture, portion size, food variety, and responsive feeding). This necessitates a concise, engaging, and easily reproducible educational approach. This study proposes the development of an animated video as a supplementary educational medium for mothers and a job-aid tool for cadres, utilizing a modified Research Development approach (Borg Gall). To create a media that is feasible, effective in increasing knowledge, and well-received by users. Methods: Included Focus Group Discussions (FGD) for needs analysis, script and storyboard design, production, expert validation, revision, and a limited pre-post-test trial involving mothers of toddlers (n=58) and cadres (n=21). Results: The media was rated as highly feasible (average 3.96/5); mothers knowledge significantly increased (61,07±15,65 → 68,39±12,18; p=0,0032; dz=0,40), and cadres' knowledge showed an greater improvement (57,88±16,43 → 71,97±11,41; p=0,0004; dz=0,92); cadre attitude was very positive (4.38/5). Discussion findings confirm that the video facilitates understanding and standardizes key messages, thereby having the potential to improve MP-ASI practices in the community. The animated video is feasible, effective, and acceptable. Recommended for integration into Posyandu Standard Operating Procedures (SOP) through short viewing/booster sessions and a one-page job-aid. Scientific article (target Sinta 1–4 journal), ready-to-use animated video product, concise job-aid sheet, and potential for Intellectual Property Rights (IPR)/cadre training module. Keywords: Animated Video, Toddler Mother’s, Cadres, Development.  ABSTRAK Pemberian makan pada 1.000 Hari Pertama Kehidupan (HPK) menentukan tumbuh kembang dan pencegahan stunting, di lapangan ibu dan kader posyandu masih menghadapi keterbatasan pengetahuan, media edukasi, serta keterampilan komunikasi. Permasalahan utama adalah rendahnya kesesuaian praktik MP-ASI (waktu mulai, tekstur, porsi, variasi, responsivitas) dengan pedoman, sehingga diperlukan pendekatan edukasi yang ringkas, menarik, dan mudah diulang. Penelitian ini mengusulkan pengembangan video animasi sebagai media pendamping ibu dan alat bantu kader, dengan pendekatan Research Development (Borg Gall, dimodifikasi). Tujuan: menghasilkan media yang layak dan efektif meningkatkan pengetahuan serta diterima pengguna. Metode meliputi FGD untuk analisis kebutuhan, perancangan naskah–storyboard, produksi, validasi ahli, revisi, dan uji terbatas pra–pasca pada ibu balita (n=58) dan kader (n=21). Hasil menunjukkan media dinilai sangat layak (rerata 3,96/5); pengetahuan ibu meningkat (61,07±15,65 →68,39±12,18; p=0,0032; dz=0,40) dan kader meningkat lebih besar (57,88±16,43 → 71,97±11,41; p=0,0004; dz=0,92); sikap kader sangat positif (4,38/5). Pembahasan menegaskan video memfasilitasi pemahaman dan menyeragamkan pesan kunci, sehingga berpotensi memperbaiki praktik MP-ASI di komunitas. video animasi layak, efektif, dan diterima; disarankan integrasi dalam SOP posyandu melalui pemutaran singkat/booster dan job-aid satu halaman. Realisasi output: artikel ilmiah (target jurnal Sinta 1–4), produk video animasi siap pakai, lembar bantu ringkas, dan potensi HKI/modul pelatihan kader. Kata Kunci: Video Animasi, Ibu Balita, Kader,  Pengembangan.